My-VRBQ: Translation and preliminary validation of the vestibular rehabilitation benefit questionnaire (VRBQ) - Mohtar, Nurul Nabila; Wan Ahmad, Wan Aslynn Salwani; Zakaria, Mohd Normani; Abdul Wahat, Nor Haniza; Mohd Sakeri, Nurul Syarida (IIUM Press, 2019)
Introduction: The purpose of this study was to translate and adapt the Vestibular Rehabilitation Benefit Questionnaire (VRBQ) into Malay (My-VRBQ). This is to add on to the limited number of vestibular questionnaire available in Malay version. Methods: After the permission from the original author was obtained, the process of adaptation began with forward-translation as well as backward translation into English, then it is followed by content and face validations. Ten participants diagnosed with vestibular problems were recruited in the My-VRBQ for validation process. They were enlisted from two hospitals in the East Coast of Malaysia. Results: Based on the comments and suggestions made by the validators; some changes in terms of the appropriateness of the instructions, items and the sentence structure were made. In the consistency analysis, the My-VRBQ revealed good internal consistency based on Cronbach alpha values (0.77 to 0.96). Conclusion: A translated and validated My-VRBQ has the potential to be used clinically to document vestibular rehabilitation benefits. Nevertheless, future studies are encouraged to further support the present study findings.